An Extensive Analysis of the 5E Learning Cycle Model and Its Impact on Student Character Development, Higher-Order Thinking, and Learning Outcomes - Eifan Boyke Pattiasina; Hasan Tuaputty; Fredy Leiwakabessy; Alwi Smith; Muhammad Tarmizi Kubangun (At- Ta'lim : Jurnal Pendidikan, 2026)
This study aims to comprehensively review the application and impact of the 5E Learning Cycle model on various aspects of learning in primary and secondary education. This research uses SLR  (Systematic Literature Review). twenty research articles published between 2017 and 2025, focusing on improving learning outcomes, science process skills, science literacy, critical and higher-order thinking skills, problem-solving skills, and character development of students. The results of the study show that the 5E Learning Cycle model, which consists of the stages of Engagement, Exploration, Explanation, Elaboration, and Evaluation, able to produce active, constructive, and meaningful learning. The consistent application of this model improves cognitive, affective, and psychomotor learning outcomes, as well as strengthening students' motivation, learning engagement, and scientific attitudes. The integration of the 5E model with various learning strategies such as mind mapping, three-dimensional thinking-based worksheets, the STEM approach, Quizwhizzer, and educational videos and games further use in building conceptual understanding and science literacy. The improvement in learning outcomes and scientific skills obtained ranged from moderate to high, with an average N-Gain score of 0.37–0.69. In addition to improving critical thinking and concept representation skills, the 5E model also contributes to the formation of social character traits such as responsibility and cooperation The 5E Learning Cycle model is a relevant and adaptive constructivist method to tackle 21st-century learning difficulties because it encourages active student participation.